The Role of Protocadherin 19 (PCDH19) in Neurodevelopment and in the Pathophysiology of Early Infantile Epileptic Encephalopathy‐9 (EIEE9). Issue 1 (18th January 2019) - Gerosa, Laura; Francolini, Maura; Bassani, Silvia; Passafaro, Maria
Abstract: PCDH19 is considered one of the most clinically relevant genes in epilepsy, second only to SCN1A . To date about 150 mutations have been identified as causative for PCDH19 ‐female epilepsy (also known as early infantile epileptic encephalopathy‐9, EIEE9), which is characterized by early onset epilepsy, intellectual disabilities, and behavioral disturbances. Although little is known about the physiological role of PCDH19 and the pathogenic mechanisms that lead to EIEE9, in this review, we will present latest researches focused on these aspects, underlining protein expression, its known functions and the mechanisms by which the protein acts, with particular interest in PCDH19 extracellular and intracellular roles in neurons.